Implementation of Eye-Tracking Technology in the Domestic Tourism Marketing Complex - Olena Sushchenko; Kateryna Kasenkova; Nataliia Pohuda; Mariana Petrova (Tourism and Hospitality)
This study explores the potential of using eye-tracking technology as a marketing tool to enhance domestic tourism. By examining the visual preferences of users, this research aims to improve the informational resources and visual components of advertising campaigns for tourism destinations. An experiment was conducted to determine which of three image categories—architecture (Ia), nature (In), and people (Ip)—captures more user attention. Participants’ eye movements were tracked to collect data on fixation time, first glance, and the order of image exploration. The findings indicate that images of people (Ip) attract more attention than images of architecture or nature, irrespective of pose, angle, or clothing. Within the Ip category, dynamic images of people in authentic clothing (Ip3–Ip5) held viewers’ attention longer, averaging 3.3 s compared to 1.3 s for static portrait photos (Ip6–Ip8). This study concludes that eye-tracking technology can effectively identify visual elements that interest potential tourists, facilitating the creation of compelling advertising content. This approach can support the development of a cohesive and engaging visual identity for tourism destinations, thereby enhancing marketing strategies and promoting sustainable tourism.